2016
DOI: 10.3390/su8101047
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Cross Laminated Timber (CLT) as an Alternative Material for Mid-Rise Residential Buildings in Cold Regions in China—A Life-Cycle Assessment Approach

Abstract: Abstract:Timber building has gained more and more attention worldwide due to it being a generic renewable material and having low environmental impact. It is widely accepted that the use of timber may be able to reduce the embodied energy of a building. However, the development of timber buildings in China is not as rapid as in some other countries. This may be because of the limitations of building regulations and technological development. Several new policies have been or are being implemented in China in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 23 publications
(22 reference statements)
3
57
0
1
Order By: Relevance
“…As mentioned above, on average, cooling and heating energy account for 35% of total energy consumption in China [7], and it can be estimated that at the national level, energy consumption in a story-story building with RC frames and CLT system are approximately 465.1 MJ/m 2 and 332.6 MJ/m 2 per annum, respectively. These results echo those outcomes from existing research [21][22][23]. Figure 9 presents the estimated results of energy consumption of RC and CLT buildings in 31 studied cities per year.…”
Section: Data Sourcesupporting
confidence: 84%
See 3 more Smart Citations
“…As mentioned above, on average, cooling and heating energy account for 35% of total energy consumption in China [7], and it can be estimated that at the national level, energy consumption in a story-story building with RC frames and CLT system are approximately 465.1 MJ/m 2 and 332.6 MJ/m 2 per annum, respectively. These results echo those outcomes from existing research [21][22][23]. Figure 9 presents the estimated results of energy consumption of RC and CLT buildings in 31 studied cities per year.…”
Section: Data Sourcesupporting
confidence: 84%
“…For the demolition stage, the destruction of a building is assumed to be 90% of the energy required in the erection phase [45]. The carbon sequestration of CLT is that one cubic meter of timber would store 1100 kg of CO2, and the on-site erection of CLT buildings is set to be 20 MJ/m 2 [22,32]. We can put this together on the basis of references above that, taking carbon storage in timber into consideration, the timber would store more carbon in itself than those emitted during the process of materialization and end-of-life stages, and more carbon reductions can be obtained if using CLT systems as an alternative to RC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al made comparisons between two seven-storey buildings constructed using RC and CLT in the severe cold region of China. They found that the energy consumption for heating and cooling was 338 MJ/m 2 and 231.2 MJ/m 2 per annum, respectively [27].…”
Section: Clt and Its Development In Chinamentioning
confidence: 99%